Emotion regulation deficits in euthymic bipolar I versus bipolar II disorder: a functional and diffusion‐tensor imaging study. (15th March 2015) - Caseras, Xavier; Murphy, Kevin; Lawrence, Natalia S; Fuentes‐Claramonte, Paola; Watts, Jessica; Jones, Derek K; Phillips, Mary L
<x xml:space="preserve">Abstract</x> Objectives Emotion regulation deficits are a core feature of bipolar disorder. However, their potential neurobiological underpinnings and existence beyond bipolar I disorder remain unexplored. Our main goal was to investigate whether both individuals with bipolar I and bipolar II disorder show deficits in emotion regulation during an attention control task, and to explore the neurophysiological underpinnings of this potential deficit. Methods Twenty healthy controls, 16 euthymic participants with bipolar I disorder, and 19 euthymic participants with bipolar II disorder completed psychometric and clinical assessments, a neuroimaging emotion regulation paradigm, and an anatomical diffusion‐weighted scan. Groups were matched for age, gender, and verbal IQ. Results During the presence of emotional distracters, subjects with bipolar I disorder showed slowed reaction times to targets, and increased blood oxygenation level‐dependent (BOLD) responses in the amygdala, accumbens, and dorsolateral prefrontal cortex, but not increased inverse functional connectivity between these prefrontal and subcortical areas, and altered white matter microstructure organization in the right uncinate fasciculus. Subjects with bipolar II disorder showed no altered reaction times, increased BOLD responses in the same brain areas, increased inverse functional connectivity between the prefrontal cortex and amygdala, and no abnormalities in white matter organization. Conclusions Participants with bipolar I disorder showed abnormalities in functional and anatomical connectivity between prefrontal cortices and subcortical structures in emotion regulation circuitry. However, these deficits did not extend to subjects with bipolar II disorder, suggesting fundamental differences in the pathophysiology of bipolar disorder subtypes.